Challenges and Opportunities of Implementing Augmented Reality (AR) and Virtual Reality (VR) in Public Universities of Afghanistan - Shahidi, Shahwali; Ali Frugh, Qurban; Kror Shahidzay, Amir (Department of Informatics, Universitas Malikussaleh, 2025)
This study explores the challenges and opportunities related to the implementation of Augmented Reality (AR) and Virtual Reality (VR) technologies in public universities in Afghanistan, with a focus on Kabul University. The research aims to assess the levels of awareness, perceived usefulness, readiness to adopt, and barriers affecting AR/VR integration in higher education. Using a quantitative research design, data were collected from 392 respondents comprising students, faculty, and administrative staff through a structured questionnaire. Descriptive analysis showed moderate awareness and positive perceptions of AR/VR’s potential benefits for enhancing learning. Inferential statistics revealed significant associations between respondents’ roles and their willingness to adopt AR/VR, as well as a strong positive relationship between digital literacy and perceived usefulness. Regression analysis identified awareness, digital literacy, and institutional support as key predictors of adoption readiness. The study highlights existing infrastructural and digital literacy challenges but emphasizes the promising potential of AR/VR to transform educational experiences in Afghan universities. The findings provide valuable insights for stakeholders aiming to promote innovative educational technologies in similar contexts.